EU Export Specialization Patterns of Selected Accession and Cohesion Countries: Tough Competition on the EU15 Market? - Borbely, Dora (Papeles del Este, 2004)
European integration brings about major impulses for structural change in industry within the enlarged European Union. Focusing on selected accession countries - Hungary, Poland and the Czech Republic - and on four cohesion countries - Spain, Portugal, Ireland and Greece - this paper presents the key shifts in sectoral developments and changing RCA indicators in exports to the EU15. A comparative analysis of the results indicates that there is intense competition among the cohesion and the accession countries as suppliers on the EU15 market. Poland and the Czech Republic are competitors mainly of Portugal and Greece in lower and middle quality goods; in some of these product groups also Hungary is a potential competitor. In addition, Hungary faces competition from Spain and Ireland in some higher quality goods. Analyzing industries according to the OECD taxonomy reveals that there is intense market participation of cohesion and accession countries in labour and resource intensive industries. However, most cohesion and accession countries have a strong comparative disadvantage on the EU15 market in science-based industries. In scale intensive industries accession countries are gaining competitive power and thus increasingly competing with cohesion countries.